2023
DOI: 10.1111/eff.12709
|View full text |Cite
|
Sign up to set email alerts
|

Influence of habitat on abundance, size and growth rate of pikeperch (Sander lucioperca) 0+ juveniles in a canyon‐shaped reservoir

Abstract: Abundance, size (standard length, LS) and growth rate of early pikeperch (Sander lucioperca) 0+ juveniles were monitored in the epipelagic and bathypelagic layers near the dam, and in the middle and upper sections at the canyon‐shaped Římov Reservoir (Czech Republic) during the day on 26 and 29 May, and during the night on 5 and 11 June in 2008. The greatest abundance of 0+ fish was observed in the middle section of the reservoir and their LS increased upstream from the dam towards the reservoir's tributary. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(62 reference statements)
1
1
0
Order By: Relevance
“…The same trend of pikeperch fry size following the trophic gradient was observed in the canyon-shaped Římov Reservoir (Blabolil et al, 2023). No obvious trend in pikeperch fry L S was observed along the longitudinal profile of the Lipno Reservoir during the summer, but an increasing trend of fry size from the dam to the upper reservoir part could be expected.…”
Section: Discussionsupporting
confidence: 62%
“…The same trend of pikeperch fry size following the trophic gradient was observed in the canyon-shaped Římov Reservoir (Blabolil et al, 2023). No obvious trend in pikeperch fry L S was observed along the longitudinal profile of the Lipno Reservoir during the summer, but an increasing trend of fry size from the dam to the upper reservoir part could be expected.…”
Section: Discussionsupporting
confidence: 62%
“…These included the generation of three genome assemblies of P. fluviatilis which will lead to improved understanding of the interactions between ecological and evolutionary processes (Vasemägi et al, 2023). Also spotlighted were geographical and within‐waterbody distribution (in particular those in reservoirs; Blabolil et al, 2023; Sajdlová et al, 2023). Changes in diet, including methods used (gut content and stable isotope analyses) to compare them (Vejříková et al, 2023), and responses to eutrophication or oligotrophication (Jůza et al, 2023), and to invasive species (Jordan et al, 2023; Yang et al, 2023), were outlined.…”
Section: Symposiummentioning
confidence: 99%
“…[6,10]). Moreover, a recent study demonstrated 0+ pikeperch diurnal vertical migration is size-dependent, as older, larger and more pigmented pikeperch migrate to the bathypelagic layer compared to younger and smaller pikeperch, who stay in the epipelagic layer during the day [22].…”
Section: Introductionmentioning
confidence: 99%